1991
DOI: 10.1346/ccmn.1991.0390302
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Swelling of Smectite Samples in Concentrated NaCl Solutions in Relation to Layer Charge

Abstract: Abstrael--The basal spacing of a set of smectites, with layer charges between 0.74 and 1.14 electrons per unit cell, have been measured while the smectites were in equilibrium with NaCI solutions having concentrations of 0.25 to 2.5 molal. Except for the most highly charged smectites, an expansion from 15.5 to ~ 18.5 ~ occurred as the NaC1 concentrations were reduced. This expansion (or "crystalline swelling") corresponds to the transition from two to three sheets of water between the silicate layers. A random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(76 citation statements)
references
References 20 publications
5
69
0
2
Order By: Relevance
“…Jaynes et al (1992) reported a decrease in the negative layer charge in Mghectorites after each of several heat treatments at 250~ which was attributed to progressive octahedral Mg > for Li + substitution. Slade et al (1991) found that the basal spacing of hectorite expanded from 15.5 .~ to 18.5 A in NaC1 solutions as the NaC1 concentration decreased, corresponding to the transition from two to three sheets of water between the silicate layers. This behavior is typical of most montmorillonites.…”
Section: Introductionmentioning
confidence: 96%
“…Jaynes et al (1992) reported a decrease in the negative layer charge in Mghectorites after each of several heat treatments at 250~ which was attributed to progressive octahedral Mg > for Li + substitution. Slade et al (1991) found that the basal spacing of hectorite expanded from 15.5 .~ to 18.5 A in NaC1 solutions as the NaC1 concentration decreased, corresponding to the transition from two to three sheets of water between the silicate layers. This behavior is typical of most montmorillonites.…”
Section: Introductionmentioning
confidence: 96%
“…The equilibrium water density of such a hydrated clay depends on the type of clay mineral, the type of interlayer counterion, the applied pressure and temperature, and the water vapor pressure. [3][4][5][6] Although clay swelling is well understood on a qualitative level, the quantitative details are difficult to access experimentally, especially on the molecular level. Statisticalmechanical computer simulations are ideally suited to obtain such microscopic insight.…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques such as NMR, IR and X-ray scattering have been used to determine the ordering and mobility of the water molecules in the layers (Nickolov et al, 2005;Pouliquen et al, 2001;Slade et al, 1991;Turov et al, 2005). Molecular dynamics simulation that combines physics, mathematics and chemistry is an advanced research method to study the radial distribution of water molecules around particles.…”
Section: Methodsmentioning
confidence: 99%